Words not Attested in Lexicographical Sources in Samuel Boguslav Chyliński’s Translation of the New Testament and Their Meaning - Thies, Felix (Vilnius University Open Series, 2018)
[full article and abstract in Lithuanian; abstract in English]This article collects all words in Chyliński’s translation of the New Testament that are not attested in the lexicographical sources (contemporary, historical and holistic dictionaries) of the Lithuanian language and analyzes their meaning based on context and etymology.